2005
DOI: 10.1002/ejic.200500125
|View full text |Cite
|
Sign up to set email alerts
|

Towards Molecular Conductors with a Spin‐Crossover Phenomenon:Crystal Structures, Magnetic Properties and Mössbauer Spectra of[Fe(salten)Mepepy][M(dmit)2] Complexes

Abstract: -units and [Fe(salten)Mepepy] cations. In the Ni compound photo-isomerisation of the Mepepy ligand can be observed in dichloromethane solution. The temperature dependence of the magnetic susceptibility of the compounds reveals a gradual S = 5/2 h S = 1/2 spin crossover of the Fe III ions. This phenomenon is confirmed by Mössbauer spectroscopy for the Ni compound, which also reveals a mag-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Hybrid materials containing SCO complexes as well as conducting molecular species in the same crystal lattice were reported by several teams [40][41][42][43][44][45][46][47][48][49][50][51][52]. Most of these compounds exhibit either SCO or semiconducting behavior or both at the same time, but (in our opinion) a clearly discernible interplay between the two phenomena has been achieved only in two cases.…”
Section: Macroscopic Samplessupporting
confidence: 58%
“…Hybrid materials containing SCO complexes as well as conducting molecular species in the same crystal lattice were reported by several teams [40][41][42][43][44][45][46][47][48][49][50][51][52]. Most of these compounds exhibit either SCO or semiconducting behavior or both at the same time, but (in our opinion) a clearly discernible interplay between the two phenomena has been achieved only in two cases.…”
Section: Macroscopic Samplessupporting
confidence: 58%
“…The interplay between spin-crossover and conductivity was already observed in some of such materials [17,[29][30][31][32][33]. The most of conducting SCO compounds represent the Fe(III) cation complexes with [M(dmit) 2 ] δ− anions [29,30,[34][35][36][37][38]. There is only one compound with TCNQ δ− , described in publications: [Fe(III)(acpa) 2 ](TCNQ) 2 , with σ rt = 2.8 10 −3 Ω −1 ·cm −1 [39].…”
Section: Introductionmentioning
confidence: 96%
“…1). This complex has been shown to exhibit a photo-induced high-spin to low-spin transition at room temperature [2][3][4]. The mepepy ligand associated with the Fe(III)(salten)(mepepy) complex is a push-pull type molecule that exhibits either a cis or trans conformation and contains an electron-withdrawing pyridyl group and an electron-donating N-methylpyrrole group, separated by an photo-isomerizable double bond.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this type of complex utilizes L = 4-sterylpyridine (Stpy) (1-phenyl-2-(4-pyridyl) ethane) as well as several phenyl derivatives to photo-induce the spin crossover [1][2][3]. It has been shown that the Fe II (trans Stpy) 4 (NCS) 2 complex undergoes a thermally induced high-spin to low-spin transition with a crossover temperature centered near 190 K [1]. Subsequent photoexcitation of this complex imbedded within a cellulose acetate substrate results in a trans to cis isomerization of the Stpy which also induces the high-spin to low-spin transition at 140 K.…”
Section: Introductionmentioning
confidence: 99%